Cargotecture in Historic Buildings: Case studies in Latin America - Medina Silva, Guillermo Gustavo (2024)
The purpose of this essay is to critically examine the advantages that repurposed shipping containers can have for the environment and for the built environment when used in historic center buildings. Also, the contribution to comprehensive solutions and without impact, of all kinds, in the historic center of Lima and other parts of the country.During this analysis, we will observe success stories where historic buildings opted for spatial solutions like maritime containers, where they contributed a significant contribution and, above all, an efficient solution for the spaces in which they were projected. Giving a clear example that this type of solutions can be applied in our historic center as a viable alternative and that, in turn, an architectural solution is being achieved that does not affect the area to be intervened. Also, in a way, contributing to the environment by recycling disused containers. Since the container, as a versatile raw material, is easy to adapt and modify if spatial needs change over time.We will also discuss the current issue of a shortage of initiatives of this sort, and how loading could be an alternative for contemplating how to intervene in ancient buildings